Is this graffiti a good ad?: Comparing street art as advertisement in Brazil and Portugal - Antunes, Narciso Emanuel Azevedo (2014)
The following thesis has as an objective to understand how city dwellers perceive street art as a means for brands and companies to advertise their products. It was meant to understand how people reacted to this kind of advertising. And how does it interact with the city and city dwellers. It was also needed to understand the artists’ point of view on the problem, their ideas towards brands who advertise in this way, and their availability to provide such works for companies and brands. Also it was necessary to interview a company using street art as advertising to understand their motivations to use it. This study is a comparison between Portugal and Brazil, where it was possible to understand differences between two countries that are in different stages of development, concerning street art. This study was developed through interviews made to Brazilian and Portuguese city dwellers and artists. The chosen company was a Portuguese one, given the limitations of the thesis and geographical closeness. This work aims at providing relevant information to companies and the academia about a worldwide phenomenon that has potential to be used in a commercial way, contributing to stronger brand equity, social and sustainable development. Also, providing relevant information to companies of how to approach artists and this kind of advertising; what do city dwellers expect from street art as advertising; and how do they cope with it.